Catalytic performances of silicotungstic acid/zirconia supported SBA-15 in an esterification of benzyl alcohol with acetic acid - Sawant, Dhanashri P.; Vinu, A.; Justus, Josena; Srinivasu, P.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2007)
Liquid phase esterification of benzyl alcohol (BA) to benzyl acetate (Peach fragrance) with an acetic acid (AA) has been investigated with 12-silicotungstic acid supported on zirconia embedded inside SBA-15 (STA/ZrO2/SBA- 15) as the catalyst. Catalysts were unambiguously characterized by XRD, N-2 adsorption-desorption, FF-IR pyridine adsorption techniques and the total amount of acidity of different STA loaded catalysts was estimated by TPD of NH3. The optimization of reaction conditions of an esterification of BA with AA was performed with 15 wt.% STA/22.4 wt.% ZrO2/SBA-15 calcined at 1123 K by varying catalyst concentration (1-10 wt.% of reaction mixture); temperature, 353-383 K and AA:BA molar ratio as 0.5-3. The 15 wt.% STA/22.4 wt.% ZrO2/SBA-15 calcined at 1123 K was found to have the highest acidity and more active in the reaction. Under the optimized reaction conditions, the 15 wt.% STA/22.4 wt.%ZrO2/SBA-15 calcined at 1123 K gave 59% BA conversion with selectivity for benzyl acetate as high as 96% within 2 h of reaction time. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: 12-silicotungstic acid; Benzyl acetate; Benzyl alcohol; Esterification; SBA-15

Benzylation of acetic acid to benzyl acetate over highly active and reusable micro/meso-HZSM-5 - Nandiwale, Kakasaheb Y.; Galande, Nitish D.; Raut, Sunil A.; Bokade, Vijay V. (Chemical Engineering Research & Design, 2015)
Catalytic benzylation of acetic acid (AA) with benzyl alcohol (BA) to benzyl acetate was studied over zeolites viz. H-ZSM-5 (microporous, medium pore), Micro/Meso-HZSM-5 (combination of micro- and meso pore), H-Beta (microporous, large pore) to investigate catalytic activity and selectivity towards benzyl acetate. Micro/Meso-HZSM-5 obtained by desilication post-treatment has been employed as a heterogeneous catalyst for benzylation reaction probably for the first time. Micro/Meso-HZSM-5 was found to be a promising catalyst for benzylation with AA conversion of 94%, selectivity towards benzyl acetate of 95%. The detailed optimization of process parameters such as molar ratio, catalyst loading, reaction temperature and time was also presented. Micro/Meso-HZSM-5 catalyst was observed to be stable for six cycles (1 fresh and 5 recycles). The first order reaction kinetics (R-2 >0.98) indicated that reaction rate constants increased with increasing reaction temperature. The activation energy for benzylation of AA with BA over Micro/Meso-HZSM-5 was obtained to be 15.07 kJ mol(-1), which is far less than the reported. (C) 2014 The Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Acetic acid; Benzyl acetate; Benzyl alcohol; Benzylation; Micro/Meso-HZSM-5; Reaction kinetics